2014
DOI: 10.1177/0748233714538484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonsteroidal anti-inflammatory meloxicam on stomach, kidney, and liver of rats

Abstract: Nonsteroidal anti-inflammatory (NSAI) drugs are the most commonly used group of drugs today. Increase in the use of standard NSAI for treating pain and inflammation was restricted by the fact that these drugs were proven to possibly cause gastrointestinal and renal toxicity. Meloxicam is a NSAI that has anti-inflammatory, analgesic, and antipyretic effects. This study aims to investigate the effects of meloxicam on stomach, kidney, and liver of rats under light microscopy level. Based on the light microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 11 publications
3
28
0
7
Order By: Relevance
“…In this study, Wistar rats that received exclusively meloxicam showed renal histological changes (basal membrane thickening and tubulointerstitial nephritis), which are in agreement with other studies [32][33][34] . On the other hand, rats that received meloxicam associated with nitrosyl ruthenium did not present such histological alterations and this is our main result.…”
Section: ■ Discussionsupporting
confidence: 93%
“…In this study, Wistar rats that received exclusively meloxicam showed renal histological changes (basal membrane thickening and tubulointerstitial nephritis), which are in agreement with other studies [32][33][34] . On the other hand, rats that received meloxicam associated with nitrosyl ruthenium did not present such histological alterations and this is our main result.…”
Section: ■ Discussionsupporting
confidence: 93%
“…Baggaley et al (2010) reported that animals dosed with meloxicam showed tubular degeneration of kidneys with hemorrhage and oedema due to decreased aquaporin-2 protein water channel expression in renal medulla after oral administration of Indomethacin and Meloxicam. Similar lesions like Glomerular stasis-related hypertrophy and focal interstitial along with the hyperemia were observed in peritubular capillaries in animals which were treated with 15mg/ kg B.W of meloxicam for 15 days (Burukoglu et al,2014). Al-Rekabi et al (2009) concluded that 2.5 million people will be affected by renal damage due to NSAIDs usage.…”
Section: Resultsmentioning
confidence: 74%
“…It is generally accepted that gastric ulcer is established when the balance between aggressive and mucosal defending factors is disrupted. 2 The Ulcer is a deep lesion of the gastric mucosa that affects the components of epithelial and connective tissue, including subepithelial myofibroblasts, smooth muscle cells, vessels, and nerves. Such ulcerative lesions can be acute or chronic and most often appear in any portion of the gastrointestinal tract exposed to the aggressive action of peptic acid.…”
Section: Introductionmentioning
confidence: 99%